Insufficient ventilation led to a probable long-range airborne transmission of SARS-CoV-2 on two buses. (January 2022) - Ou, Cuiyun; Hu, Shixiong; Luo, Kaiwei; Yang, Hongyu; Hang, Jian; Cheng, Pan; Hai, Zheng; Xiao, Shanliang; Qian, Hua; Xiao, Shenglan; Jing, Xinping; Xie, Zhengshen; et al.
Abstract: Uncertainty remains on the threshold of ventilation rate in airborne transmission of SARS-CoV-2. We analyzed a COVID-19 outbreak in January 2020 in Hunan Province, China, involving an infected 24-year-old man, Mr. X, taking two subsequent buses, B1 and B2, in the same afternoon. We investigated the possibility of airborne transmission and the ventilation conditions for its occurrence. The ventilation rates on the buses were measured using a tracer-concentration decay method with the original driver on the original route. We measured and calculated the spread of the exhaled virus-laden droplet tracer from the suspected index case. Ten additional passengers were found to be infected, with seven of them (including one asymptomatic) on B1 and two on B2 when Mr. X was present, and one passenger infected on the subsequent B1 trip. B1 and B2 had time-averaged ventilation rates of approximately 1.7 and 3.2 L/s per person, respectively. The difference in ventilation rates and exposure time could explain why B1 had a higher attack rate than B2. Airborne transmission due to poor ventilation below 3.2 L/s played a role in this two-bus outbreak of COVID-19. Graphical abstract: Image 1 Highlights: Ten passengers were infected on two buses by an index case. Time-averaged ventilation rates were 1.72 and 3.22 L/s per person on two buses respectively. Lower ventilation rate and exposure time led to higher attack rate. Insufficient ventilation played a role in this two-bus outbreak of COVID-19. Providing sufficient ventilation reduces infection.